Neuromyths in Industrial and Organisational Psychology in South Africa: Prevalence and impact - Ingra du Buisson-Narsai; Talia Fisher; Andrew Morris; Xander van Lill (SA Journal of Industrial Psychology, 2024)
Orientation: Industrial Psychologists (IPs) could significantly benefit from integrating neuroscientific evidence into their practices, provided they critically engage with scholarly research rather than rely on unsupported assertions.